2018
DOI: 10.3769/radioisotopes.67.435
|View full text |Cite
|
Sign up to set email alerts
|

Natural Radioactivity Measurements in Soil, External Dose and Radiological Hazard Assessment in the Uranium and Thorium Bearing Region of Lolodorf, Cameroon

Abstract: The level of natural radioactivity has been evaluated for soil samples collected from the uranium and thorium bearing region of Lolodorf in the southwestern Cameroon. Specific activities of 226 Ra, 232 Th and 40 K in these soil samples were determined using γ-ray spectrometry with sodium iodide (NaI(Tl)) detector. The specific activities for the whole study areas where consist of five inhabited localities were compared with the world average and permissible recommended limits. Specific activities of 226 Ra, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The characteristics of the dwellings selected in this study also justify their high values. In addition, previous study carried out in the same study areas of this study revealed the presence of the anomaly of 232 Th and 238 U at some specific points in the region (24,27,28). However, the literature (29) has revealed a strong link between EETC on the one hand, and type of architecture, geology, climate and people's lifestyle on the other.…”
Section: Radon Thoron and Thoron Progeny Concentrationssupporting
confidence: 41%
“…The characteristics of the dwellings selected in this study also justify their high values. In addition, previous study carried out in the same study areas of this study revealed the presence of the anomaly of 232 Th and 238 U at some specific points in the region (24,27,28). However, the literature (29) has revealed a strong link between EETC on the one hand, and type of architecture, geology, climate and people's lifestyle on the other.…”
Section: Radon Thoron and Thoron Progeny Concentrationssupporting
confidence: 41%
“…The longer experiment, the more accurate spectrum and thus better assessment of the radioactivity concentration. Typical time e.g., for soil radioactivity measurements varies from several up to 72 h, see [20,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…The dried dust was sieved through 2 mm sieves. This procedure assures quite good homogeneity of the samples for testing the radioactivity concentrations, [15][16][17][18][19][20]. The samples prepared in this way were then poured into 1.5 dm 3 cylindrical Marinelli beakers, then placed under the spectrometer probe.…”
Section: Sample Preparation For Gamma Spectrometrymentioning
confidence: 99%
“…It was stated that the construction year of the building had the highest impact on the difference in indoor radon concentration among schools. According to the results of indoor radon measurements conducted in Cameroon, the average indoor radon concentration value exhibited a low-risk level compared to the permissible limits, with a value of 42 Bqm −3 [241]. The annual arithmetic average of the radon concentration in Beijing obtained was 42 ± 13.7 Bqm −3 [242].…”
Section: Indoor Radon Concentrationmentioning
confidence: 97%